Characteristics of the professionals and the extensionist work at Empaer-MT faced with the challenges of National Policy on Technical Assistance and Rural Extension (Emancipação, 2022)
This paper aimed to characterize the profile of the professionals and the extensionist work of the Company for Agricultural Research, Assistance and Rural Extension of the State of Mato Grosso (Empaer-MT-Brazil), and analyze its compatibility to assumptions of the National Policy on Technical Assistance and Rural Extension (PNATER). The research consisted in the application of a questionnaire with the 62 local extension workers of the referred Company. It was evident that, faced with the challenges proposed by the institutionalization of PNATER, the aspects directed to the extensionist action have acquired greater relevance than the professional profile, as well as the initial and continuing training actions demonstrated to be essential to the creation of a reflective and critical environment, as provided for in the Policy.